Comparative Genomic Analysis and a Novel Set of Missense Mutation of the Leptospira weilii Serogroup Mini From the Urine of Asymptomatic Dogs in Thailand - Kurilung, Alongkorn; Perreten, Vincent; Prapasarakul, Nuvee (Frontiers in Microbiology, 2021)
Leptospira weilii belongs to the pathogenic Leptospira group and is a causal agent of human and animal leptospirosis in many world regions. Leptospira weilii can produce varied clinical presentations from asymptomatic through acute to chronic infections and occupy several ecological niches. Nevertheless, the genomic feature and genetic basis behind the host adaptability of L. weilii remain elusive due to limited information. Therefore, this study aimed to examine the complete circular genomes of two new L. weilii serogroup Mini strains (CUDO6 and CUD13) recovered from the urine of asymptomatic dogs in Thailand and then compared with the 17 genomes available for L. weilii. Variant calling analysis was also undertaken to gain potential insight into the missense mutations, focusing on the known pathogenesis-related genes. Whole genome sequences revealed that the CUDO6 and CUD13 strains each contained two chromosomes and one plasmid, with average genome size and G+C content of 4.37 Mbp and 40.7%, respectively. Both strains harbored almost all the confirmed pathogenesis-related genes in Leptospira. Two novel plasmid sequences, pDO6 and pD13, were identified in the strains CUDO6 and CUD13. Both plasmids contained genes responsible for stress response that may play important roles in bacterial adaptation during persistence in the kidneys. The core-single nucleotide polymorphisms phylogeny demonstrated that both strains had a close genetic relationship. Amongst the 19 L. weilii strains analyzed, the pan-genome analysis showed an open pan-genome structure, correlated with their high genetic diversity. Variant calling analysis identified missense mutations in genes involved in endoflagella, LPS structure, mammalian cell entry protein, and hemolytic activities, and may be associated with host-adaptation in the strains. Missense mutations of the endoflagella genes of CUDO6 and CUD13 were associated with loss of motility. These findings extend the knowledge about the pathogenic molecular mechanisms and genomic evolution of this important zoonotic pathogen.